Human immunoglobulin treatment of multifocal motor neuropathy and polyneuropathy associated with monoclonal gammopathy. (November 1994) - Leger, J M; Younes-Chennoufi, A B; Chassande, B; Davila, G; Bouche, P; Baumann, N; Brunet, P
Abstract : Intravenous human immune globulin (IVIg) has been proposed for the treatment of various peripheral neuropathies that are considered to be immunemediated. The results are reported of an open trial conducted in multifocal motor neuropathy and polyneuropathy associated with monoclonal gammopathy. Six cases with multifocal motor neuropathy, selected on clinical and electrophysiological criteria (four of six patients also had significantly high anti-GM1 titres), received IVIg monthly, at doses varying from 1.6 to 2.5 mg/kg, over three to 13 months. The initial response to treatment was dramatic in 3/6 cases (with improvement of at least two grades on the MRC scale in the five more severely affected muscles). The final evaluation showed a good result in 4/6 cases, but the conduction blocks were not significantly reduced. In 13 other cases with polyneuropathy associated with IgM monoclonal gammopathy of unknown significance, IVIg was of benefit, with improvement of at least one grade on the Prineas score, in 4/7 cases previously treated with immunosuppression and 2/3 cases not treated before IVIg. In the last group of four patients with polyneuropathy and IgG monoclonal gammopathy, IVIg was followed by clinical improvement in the two cases with a chronic demyelinating polyneuropathy.